Application of Open Source Electronics for Studying High Frequency Urban Heat Island - Ferrelli, Federico (2016)
A new measurement system based on open source electronics (Arduino) was designed to obtain high frequency data to study Urban Heat Island (UHI). The instrument registers geo-referenced information of air temperature, relative humidity, barometric pressure and altitude above sea level in a moving vehicle. The device was designed to analyze the UHI in Bahia Blanca city, Argentina. Measurements were made with the method of urban transects during different days of summer and winter. The spatial distribution of air temperature was associated with wind direction and speed. Relative humidity was low in the downtown area and high in the periphery and the estuarine coast. In conclusion, the device allowed to study the Urban Heat Island in the city. Its use will be useful for urban planning because the measurements are very fast and accurate.